ANALISIS PENGARUH ARUS PADA PENGELASAN BERTINGKAT (MULTILAYER WELDING) TERHADAP STRUKTUR MIKRO, KEKERASAN DAN KUAT TARIK SAMBUNGAN MATERIAL ASTM A106 - Elkana Bilak Lopo; Moch Chamim; Nugroho Tri Atmoko; Margono Margono; Hendi Lilih Wijayanto (Jurnal Rekayasa Mesin, 2023)
This aims of this study to determine the effect of multilayer welding on ASTM A106 type carbon steel pipe material on the characteristics of the microstructure, hardness and maximum tensile strength of the material. ASTM A106 type carbon steel pipe is used as a raw material for welding using the Shielded Metal Arc Welding (SMAW) method. Welding on material joints is carried out in three layers (multilayer welding), namely the root pass, hot pass, and capping layers. There are two variations of welding specimens carried out in this study, namely in specimen 1 the currents used were 60, 70 and 80 A while in specimen 2 the currents used were 70, 80 and 90 A. To determine the effect of current variations on each specimen carried out three include Vickers Testing, microstructure testing and tensile testing. The results show that the base metal area is dominated by the ferrite phase, which indicates that the area has low hardness while the weld shows more perlite phase than ferrite besides the grain size is smaller and denser; this indicates that the hardness level will increase when compared to base metal. The results of the hardness test for all variations of the specimen concluded that the highest hardness value was in the weld. From the tensile test, it can be concluded that specimen 2 has a greater tensile strength of 2.5% when compared to specimen 1.